Deadlock detection and resolution in automated material handling system - Huang, BianXun. (2013)
Adoption of automated guided vehicles (AGVs) by container terminals has been rapid in recent years. This is especially true in Singapore, with PSA International Pte. Ltd seeking to develop AGVs prototype in bid to increase their efficiency and throughput. However, there is a possibility where the quay cranes, stacking cranes and AGVs request for each other directly or indirectly to start a loading or unloading operation. This leads to a halt among the affected resources and creates a condition call deadlock.